Fly Ash Particle Size Effect on Pore Structure and Strength of Fly Ash Foamed Geopolymer - Luchang Xiong; Zhijun Wan; Yuan Zhang; Fangtian Wang; Junhui Wang; Yanlei Kang (Advances in Polymer Technology, 2019)
The aim of this paper is to study the particle size effect of fly ash (FLA) on pore structure and strength of Fly Ash Foamed Geopolymer (FAFG). Information on the macro-pores such as macro-pore size and distribution of FAFG is captured through binarization processing. Porosity and compressive strength of FAFG are respectively tested by Archimedes density test method and uniaxial compressive strength test method. It can be concluded that the FLA particle size has an effect on the pore structure and strength of FAFG. More specifically, the effect of FLA particle size shows itself macroscopically on the quantity of middle and large macro-pores and the uniformity of macro-pores distribution, and microscopically on the quantity of micro-holes and cracks and calcium silicate (C-S-H) quantity at the early stage of FAFG mixture. All of the properties of FAFG follow some kind of changing rule except at the turning point when FLA particle is of 0.125~0.25 mm in size. To explain clearly the root cause of FLA particle size effect on FAFG, SEM, and XRD are employed to explore the microstructure of FAFG and the component of FLA. It turns out to be the amorphous phase SiO2 content in FLA of different particle sizes which could determine the reaction extent of FAFG mixture.